2013
DOI: 10.5194/nhess-13-2441-2013
|View full text |Cite
|
Sign up to set email alerts
|

Are great Cascadia earthquakes recorded in the sedimentary records from small forearc lakes?

Abstract: Abstract. Here we investigate sedimentary records from four small inland lakes located in the southern Cascadia forearc region for evidence of earthquakes. Three of these lakes are in the Klamath Mountains near the Oregon-California border, and one is in the central Oregon Coast range. The sedimentary sequences recovered from these lakes are composed of normal lake sediment interbedded with disturbance event layers. The thickest of these layers are graded, and appear to be turbidites or linked debrites (turbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 124 publications
(168 reference statements)
1
46
0
Order By: Relevance
“…Sediment sequences containing MTDs have widely been used successfully for paleoseismic studies. Recently, for example, this approach has been applied effectively in the Cascadia region (Adams, 1996;Goldfinger et al, 2007;Goldfinger et al, 2003;Morey et al, 2013), France (Chapron et al, 1999;Wilhelm et al, 2016), British Columbia, Canada (Blais-Stevens & Clague, 2001), Switzerland (Schnellmann et al, 2006;Strasser et al, 2013), Chile (Blumberg et al, 2008;Moernaut et al, 2014), and Turkey (Avşar et al, 2016;Schwab et al, 2009). Earthquake triggering for mass transport at Lake Lisan (paleo-Dead Sea) is supported by its location on the seismically active Dead Sea Transform (DST) and by the on-shore association of deformations associated with faulting (Marco & Agnon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sediment sequences containing MTDs have widely been used successfully for paleoseismic studies. Recently, for example, this approach has been applied effectively in the Cascadia region (Adams, 1996;Goldfinger et al, 2007;Goldfinger et al, 2003;Morey et al, 2013), France (Chapron et al, 1999;Wilhelm et al, 2016), British Columbia, Canada (Blais-Stevens & Clague, 2001), Switzerland (Schnellmann et al, 2006;Strasser et al, 2013), Chile (Blumberg et al, 2008;Moernaut et al, 2014), and Turkey (Avşar et al, 2016;Schwab et al, 2009). Earthquake triggering for mass transport at Lake Lisan (paleo-Dead Sea) is supported by its location on the seismically active Dead Sea Transform (DST) and by the on-shore association of deformations associated with faulting (Marco & Agnon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Flood‐transported minerogenic sediments require a supply of sediment that is generated by weathering and punctuated by mass movements. Landsliding is common in the Condrey Mountain schist in the watershed (Figure ); such landslides may be associated with extreme precipitation, though a previous study matched some of the larger events in the core with earthquake events identified at the coast (Morey et al ., ). Forest fires are also common within the watershed; Colombaroli and Gavin () noted that many silt layers followed charcoal peaks suggesting a major role of fire in controlling forest dynamic over centuries, and amplifying the effect of hydrology on erosion.…”
Section: Methodsmentioning
confidence: 97%
“…Upper Squaw Lake in the Siskiyou region of Oregon and California provides an excellent case study to investigate such controls on catchment erosion because the charcoal record shows that fires of both low and high severity have been a key driver for vegetation structure and composition over millennia, affecting slope stability and therefore post‐fire erosion events (Colombaroli and Gavin, ). In addition, the availability of regional Late Holocene records for earthquake events (Morey et al ., ), Pacific Northwest summer temperature (Mann et al ., ), and regional winter precipitation and temperature (Ersek et al ., ), allow direct comparison between multiple external controls. Furthermore, the onset of logging in the catchment over recent decades, which increased sediment fluxes (Colombaroli and Gavin, ; Richardson et al ., ), enables a comparison of natural versus anthropogenic controls on sediment flux.…”
Section: Introductionmentioning
confidence: 99%
“…Today, many studies use various forms of instantaneously formed sedimentary deposits or structures for qualitative and quantitative earthquake reconstructions in lacustrine systems during the Holocene, as long as the seismic origin of these deposits is clear. Most of these studies are concentrated in tectonically active regions such as the Alps (Beck et al, 1996;Schnellmann et al, 2002;Monecke et al, 2004;Nomade et al, 2005;Strasser et al, 2006Strasser et al, , 2013Wilhelm et al, 2015;Chapron et al, 2016), the Anatolian fault (Schwab et al, 2009;Avşar et al, 2014Avşar et al, , 2015 and around the Pacific where recurrent and large earthquakes have been recently experienced such as in Chile (Chapron et al, 2006;Bertrand et al, 2008;Moernaut et al, 2007Moernaut et al, , 2014, US western coast (Karlin et al, 2004;Maloney et al, 2013;Morey et al, 2013;Smith et al, 2013), Japan (Inouchi et al, 1996) or New Zealand (Howarth et al, 2014;Gomez et al, 2015). Moreover, recent limnogeological investigations in glacial lakes of the mid-continental North America underline the ability of sediment to archive earthquakes throughout the Holocene, despite the low to moderate magnitude of earthquakes that occurred in this intraplate domain (St-Onge et al, 2004;Doughty et al, 2014;Lajeunesse et al, in press;Locat et al, 2016).…”
mentioning
confidence: 99%